2015
DOI: 10.3126/kumj.v12i2.13651
|View full text |Cite
|
Sign up to set email alerts
|

Use of Head Circumference as a Predictor of Height of Individual

Abstract: Background Establishing personal identity is one of the main concerns in forensic investigations. In forensic anthropology, estimation of height from head circumference has a significant role in establishing personal identity.Objective The objective of the present study was an attempt to understand the relationship between height and head circumference of an individual and to derive regression formulae to estimate the height from the head circumference.Method The present study consisted of 440 (258 male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Also, in another study (Nemade et al 2015), the correlation of head circumference, length, and width with body height was found to be significant and positive. A significant positive correlation of stature with the head length and width (Agarwal et al 2014), head length (Chourasia et al 2014), and head circumference (Mansur et al 2014) have also been reported. Also, a significant correlation was found between the height and head dimensions (head circumference, length, and width) in another study (Kumar and Gopichand 2013;Singh 2013).…”
Section: Introductionmentioning
confidence: 78%
“…Also, in another study (Nemade et al 2015), the correlation of head circumference, length, and width with body height was found to be significant and positive. A significant positive correlation of stature with the head length and width (Agarwal et al 2014), head length (Chourasia et al 2014), and head circumference (Mansur et al 2014) have also been reported. Also, a significant correlation was found between the height and head dimensions (head circumference, length, and width) in another study (Kumar and Gopichand 2013;Singh 2013).…”
Section: Introductionmentioning
confidence: 78%
“…Considering this fact, the authors attempted to correlate the volume of the sinuses with the head circumference, as the literature states that there is a strong association between the head circumference and body size. 15,16 It was not possible to correlate the volume of the sinuses with the height, weight and body size of the patients in the present study, as this study was retrospective. The Pearson correlation between the mean volume of the sinuses and the head circumference was assessed in terms of sig-nificance.…”
Section: Discussionmentioning
confidence: 91%
“…Head circumference is also a significant craniofacial criterion which can be used for gender determination, as the literature states that there is a strong association between head circumference and body size. 15,16 Thus, the correlation between the volume of the maxillary sinus and the head circumference can provide additional information with regard to the utility of the maxillary sinuses in gender determination.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation coefficients between the personal stature and OFC among Sri Lankans were found to be statistically significant and positive (0.62 in male and 0.86 in female) indicating a strong relationship between the two parameters. Previous studies have shown correlation coefficients of 0.78 in North Indian males (Krishan), 0.44 in Nepalese male and 0.32 Nepalese females 0.32 (Mansur et al, 2014), 0.4 in Bangladesh male and 0.3 in Bangladesh female (Akhter et al, 2009). 0.34 in Canadian male (Nguyen et al).…”
Section: Discussionmentioning
confidence: 94%